Dialectical engagement with biblical narratives in Ibn ‘Ashur's Tafsīr Al-Taḥrīr wa Al-Tanwīr: Study of Aaron, Jesus, and Noah's Wife narratives - Hurnawijaya; Auladi, Akrom; Fitriana, Nur; Khaqiqi, Ahmad Faruq; Mutiara M; Ningrum, Ulfia; Nadila, Tika; Haikal, M. Arsyad; Alfi, ⁠Syifa Urrachmi Nurul; Nurilhilmah; Arsyad, ⁠Najwah (Research Journal in Advanced Humanities, 2025)
The historical marginalization of direct engagement with Biblical texts within Islamic exegetical traditions has contributed to an ahistorical perception of the Qur'ān's narrative relationship with Judeo-Christian traditions. While classical mufassirūn (exegetes) predominantly relied on orally transmitted Isrā'īliyyāt narratives rather than engaging directly with Biblical texts, this methodological limitation began to shift significantly in the colonial era. This article examines the critical dialectic methodology employed by Muhammad al-Tahir Ibn 'Ashur (1879-1973) in his magnum opus, al-Taḥrīr wa al-Tanwīr, as a pivotal epistemological intervention in modernist Qur'anic hermeneutics. Operating within the complex socio-intellectual landscape of French colonial Tunisia, Ibn ‘Āshūr developed a sophisticated hermeneutical framework that directly engaged Biblical texts while simultaneously challenging their narratological authority. Through comparative textual analysis of three paradigmatic narratives—the Golden Calf episode (QS. Ṭāhā), the Christology of Jesus/'Isa (QS. Maryam), and the status of Noah's wife (QS. Taḥrīm)—this study reveals how Ibn 'Ashur's critical dialectic represents an epistemological negotiation between traditional Islamic exegetical principles and modern text-critical methodologies. The findings demonstrate that Ibn 'Ashur's approach transcends mere apologetics by constructing a multi-layered hermeneutical framework that simultaneously validates the Qur'anic narrative through rational argumentation, historical contextualization, and linguistic analysis while positioning it as an epistemologically superior corrective to perceived Biblical inconsistencies. This research contributes to the evolving understanding of Muslim intellectual responses to modernity and colonialism through textual engagement, revealing how comparative scriptural hermeneutics functioned as both intellectual resistance and epistemological restructuring in early 20th century Islamic reformism